2013
DOI: 10.1186/bcr3409
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled phase II trial of pre-operative celecoxib treatment reveals anti-tumour transcriptional response in primary breast cancer

Abstract: IntroductionCyclooxygenase-2 (COX-2) is frequently over-expressed in primary breast cancer. In transgenic breast cancer models, over-expression of COX-2 leads to tumour formation while COX-2 inhibition exerts anti-tumour effects in breast cancer cell lines. To further determine the effect of COX-2 inhibition in primary breast cancer, we aimed to identify transcriptional changes in breast cancer tissues of patients treated with the selective COX-2 inhibitor celecoxib.MethodsIn a single-centre double-blind phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 52 publications
2
54
0
1
Order By: Relevance
“…Celecoxib alone has been evaluated in previous breast cancer presurgical studies with contradictory results: Martin and colleagues showed mainly null results with 400 mg/day treated for 2 weeks (52), whereas Brandão and colleagues used 400 mg twice a day for 2 to 3 weeks and showed a significant Ki-67 reduction (53). Both studies evaluated a relatively small group of subjects.…”
Section: Discussionmentioning
confidence: 97%
“…Celecoxib alone has been evaluated in previous breast cancer presurgical studies with contradictory results: Martin and colleagues showed mainly null results with 400 mg/day treated for 2 weeks (52), whereas Brandão and colleagues used 400 mg twice a day for 2 to 3 weeks and showed a significant Ki-67 reduction (53). Both studies evaluated a relatively small group of subjects.…”
Section: Discussionmentioning
confidence: 97%
“…A clinical study in breast cancer showed that pre-operative celecoxib treatment sets up transcriptional programs supporting anti-tumor activity61. Several other trials demonstrated the use of combination of celecoxib and aromatase inhibitors in the neoadjuvant treatment is effective in reducing breast tumor size and area626364.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Dai et al [20] and Brandao et al [29] showed that Celecoxib inhibits the proliferation of breast cancer.…”
Section: Discussionmentioning
confidence: 99%